Multi-Component Thermal Fluid Injection Performance in Recovery of Heavy Oil Reservoirs - Qin, Jianhua; Zhang, Jing; Zhu, Shijie; Wang, Yingwei; Wan, Tao (Frontiers in Energy Research, 2021)
Field observations discern that the oil production rate decreases substantially and water cut increases rapidly with increase of steam injection cycles. Compared with steam drive, the advantage of flue gas (also called multi component thermal gases) co-injection with steam is that flue gas can increase the reservoir pressure and expand the heating chamber. In this paper, the flue gas generated by fuel burning in the field was injected with steam to improve heavy oil recovery. This technique was investigated in the laboratory 3D large model and implemented in the field as well. The huff-n-puff process efficiency by flue gas, steam, and flue gas-steam coinjection were compared in the experiments. The field practice also demonstrated that addition of non-condensable gas in the steam huff-n-puff process recovered more oil than steam alone. The temperature profile in the wellbore with flue gas injection is higher than the steam injection since the low thermal conductivity of N2 reduces the heat loss. With the increase of stimulation cycles, the incremental oil recovery by flue gas injection declines significantly.